Biophysical characterization of natural antimicrobials towards development of antibacterial skin therapies - Valle González, Elba Ruth (Nanyang Technological University, 2021)
Acne vulgaris and atopic dermatitis are the world’s most common skin diseases. Both are associated with the overgrowth of Cutibacterium acnes bacteria (formerly known as Propionibacterium acnes) for the first one and Staphylococcus aureus for the second. While direct inhibition of C. acnes and S. aureus can improve therapeutic outcomes, this goal is difficult to achieve due to the growing rise of antibiotic-resistant strains and current therapies rely mainly on ameliorating disease symptoms. Improved treatment strategies are needed to directly inhibit C. acnes and S. aureus, and mitigate disease symptoms. One promising bioinspired option involves utilizing natural antimicrobial lipids and glycolic acid. Antimicrobial lipids are found in the epidermis and are designed to protect against undesired bacteria and regulate the microbiome. Glycolic acid is a well-known compound in skincare used to diminish wrinkles and marks. To further improve the cutaneous delivery of the formulation with antimicrobial lipids, bicelles were devised. Bicelles are a new type of nanocarriers that have proved to be effective in dermal uptakes by guaranteeing the local effect, skin appendage penetration and time controlled delivery. The overall hypothesis of this thesis was that the therapeutic activities of the antimicrobial lipids assembled as bicelles and glycolic acid can be employed in additive multifunctional combination to treat C. acnes and S. aureus infections. To test the hypothesis, an integrated combination of chemical, physical and biological experimental approaches were undertaken. First the antibacterial effect of antimicrobial lipids, namely lauric acid and glycerol monolaurate, was characterized by employing model membrane platforms and establishing correlations with antibacterial activity. Secondly, the anti-infective activity of glycolic acid against C. acnes was evaluated. The mechanism by which glycolic acid destroys the cell membrane was determined using a fluorescent counterstaining technique to distinguish live and dead cells, and by monitoring a sensitive marker for membrane damage. Third, bicelles were developed for the protection, delivery and effect enhancement of the antimicrobial lipid on skin. The bicelles size was resolved with light scattering and electron microscopy to match it with the antimicrobial activity. Finally, the cell proliferation and viability were tested over human immortalized keratinocyte cells (HaCaT) to prove its safeness. Taken together these outcomes, it was proven that glycerol monolaurate and glycolic acid are a viable and feasible solution to treat C. acnes and S. aureus infections. It provide mechanistic insight into how antimicrobial lipids, glycolic acid and bicelles with glycerol monolaurate operate and destroy bacterial membranes under skin-relevant environmental conditions.